New Multiple Choice Formats: The Omission Item - Hanspeter Bauer; Helmut Bonheim (Miscelánea: A Journal of English and American Studies, 1996)
The omission item in a multiple choice test consists of a text in which four or five words or phrases are marked, only one of which is essential to the grammatical, syntactic or logical coherence of the text. Such items have a number of advantages: they allow authentic language materials to be used; a wide range of facility indices can be achieved, including those required for advanced and sophisticated learners of English as a foreign language as well as native speakers; the discrimination indices are unusually high, which suggests that the item taps layers of ability in understanding difficult texts. The format allows a number of variations: the key can be defined as the string which is essential, but also the string which is disposable (mere verbiage or deadwood). Half a dozen examples of these types is presented, together with the results of a factor analysis based on trials involving up to 500 candidates.